Metaphors of Life Insurance and Home Appliance on Youtube Advertisements Videos - Lilik Rochmah Agustina; Masriatus Sholikhah (Diglossia: Jurnal Kajian Ilmiah Kebahasaan dan Kesusastraan, 2017)
AbstractThe aim of this research is to explore metaphors in life insurance and home appliance on YouTube advertisements videos by employing pragmatics perspective. To accomplish the goal of the research, qualitative descriptive is employed to figure out of both two research questions. Furthermore, to know the kinds of metaphor, researchers work on theory proposed by Lakoff and Johnsen (2003) for fundamental metaphor theory, then, conceptual metaphor theory proposed by Kovecses (2010); and the last is pictorial metaphor theory proposed by Forceville (2002). At last, it can be seen that the type of metaphor are pictorial metaphor for SINAR MAS MSIG life insurance and LG home appliance advertisements. Further, in term of conceptual metaphor researchers found two type of metaphor; structural metaphor and ontological metaphor in Thai life insurance and Philips home appliance advertisements. As the closing, researchers figured out that among the four of life insurance and home appliance advertisements issued in YouTube apply the persuasive strategy to influence the audiences. These advertisements eventually are influential in inviting customers’ attention since the application of metaphors and persuasive strategies.Keywords: Metaphor, Source Domain, Target Domain, YouTube Advertisement Video, Persuasion   AbstrakPenelitian ini bertujuan untuk menyelidiki metaphor yang terdapat pada video iklan asuansi jiwa dan iklan perabot rumah tangga di laman Youtube melalui pendekatan Pragmatic. Untuk mencapai tujuan penelitian, pendekatan kualitatif diaplikasikan untuk menjawab dua permasalahan penelitian. Lebih lanjut, untuk mengetahui jenis metafor yang digunakan pada objek penelitian, peneliti menggunakan teori dari Lakoff dan Johnsen (2013) tentang Fundamental Metaphor, Conseptual Metaphor dari Kovecses (2010), dan teori Pictorial Metaphor dari Forceville (2002). Akhirnya, dapat diketahui bahwa jenis metaphor yang di temukan dalam empat iklan di laman Youtube adalah pada iklan asuransi jiwa Sinar Mas MISG life dan iklan perabot rumah tangga LG terdapat lebih dominan Pictorial Metaphor. Selain itu, pada iklan asuransi jiwa Thailand dan iklan lampu Philip cenderung menggunakan Conceptual Metaphor dengan temuan 2 sub jenis dominan yakni Structural Metaphor dan Ontoligical Metaphor. Sebagai penghujung temuan, peneliti menemukan fakta bahwa keempat iklan asuransi jiwa dan iklan perabot rumah tangga yang ditayangkan pada laman Youtube menggunakan beberapa jenis strategy persuasive untuk mempengaruhi khalayak. Secara jelas, iklan-iklan tersebut bersift persuasive dalam mengundang perhatian dan minat para konsumen dengan menggunakan unsur-unsur metafora dan strategi persuasif.     Kata kunci: metafora, domain sumber, domain target, video iklan mber, domain target, video iklan Youtube, persuasi.